Burn injury causes mitochondrial dysfunction in skeletal muscle - Padfield, Katie E. (National Academy of Sciences, 2005)
Severe burn trauma is generally followed by a catabolic response that leads to muscle wasting and weakness affecting skeletal musculature. Here, we perform whole-genome expression and in vivo NMR spectroscopy studies to define respectively the full set of burn-induced changes in skeletal muscle gene expression and the role of mitochondria in the altered energy expenditure exhibited by burn patients. Our results show 1,136 genes differentially expressed in a mouse hind limb burn model and identify expression pattern changes of genes involved in muscle development, protein degradation and biosynthesis, inflammation, and mitochondrial energy and metabolism. To assess further the role of mitochondria in burn injury, we performed in vivo (31)P NMR spectroscopy on hind limb skeletal muscle, to noninvasively measure high-energy phosphates and the effect of magnetization transfer on inorganic phosphate (P(i)) and phosphocreatine (PCr) resonances during saturation of γATP resonance, mediated by the ATP synthesis reactions. Although local burn injury does not alter high-energy phosphates or pH, apart from PCr reduction, it does significantly reduce the rate of ATP synthesis, to further implicate a role for mitochondria in burn trauma. These results, in conjunction with our genomic results showing down-regulation of mitochondrial oxidative phosphorylation and related functions, strongly suggest alterations in mitochondrial-directed energy expenditure reactions, advancing our understanding of skeletal muscle dysfunction suffered by burn injury patients.